2017
DOI: 10.3906/sag-1601-149
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sjögren’s syndrome in patients with celiac disease

Abstract: Background/aim: Many autoimmune diseases occur concomitantly with celiac disease (CD). We aimed to determine the frequency of Sjögren's syndrome (SS) in CD patients based on SS-specific serology verified by minor labial salivary biopsy.Materials and methods: Eight-two patients with CD were included in the study. After examination for objective evidence of sicca complex, all patients were tested for serological presence of rheumatoid factor (RF) and antinuclear antibodies (ANAs) and for ANA profile. Minor labia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Some studies have shown a relationship between CD and ocular surface diseases, like dry eye. Dendritic cells and natural killer B and T cells are responsible for ocular surface inflammation [7, 8]. Besides the autoimmune response, deficiencies of vitamins due to malabsorption might contribute to dry eye in CD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown a relationship between CD and ocular surface diseases, like dry eye. Dendritic cells and natural killer B and T cells are responsible for ocular surface inflammation [7, 8]. Besides the autoimmune response, deficiencies of vitamins due to malabsorption might contribute to dry eye in CD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Ayar et al[ 29 ] found a high frequency of dry eye/mouth in CD patients, with approximately one in four being symptomatic, but only few had a biopsy-based diagnosis of SS; the frequency of SS classified according to the 2012 ACR or to American-European Consensus Group criteria was 4.9%[ 29 ]. Similarly, in a small cohort of 82 CD patients, Erbasan et al[ 25 ] reported a high prevalence of dry eye (29.3%) and dry mouth (24.4%) symptoms; in this group, the diagnosis of SS was proven by biopsy in 1.2% of CD patients[ 25 ]. Moreover, four patients (4.9%) were diagnosed with undifferentiated connective tissue disease, two of them being positive for anti-SS-A/La antibodies, but having though negative biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other authors have also looked at the SS occurrence in CD patients, results of which are summarized in Table 2 [ 25 - 29 ]. Using the California criteria for SS, Collin et al[ 28 ] reported a prevalence of 3.3% for SS in patients with CD, a significant association in contrast with other connective tissue disease[ 28 ], while Caglar et al[ 27 ] reported a prevalence of 6.5% (SS-A/SS-B antibody)[ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uzel et al 19 demonstrated that tear film break-up time and Schirmer test results were significantly lower and Goblet cell count remarkably diminished in CD. We did not test the tear film break-up time and Schirmer in our study but measured the corneal thickness by OCT. Primary Sjögren's syndrome is extremely rare in disease 20 . There are very few reports of posterior segment thickness measurements in CD-related literature.…”
Section: Discussionmentioning
confidence: 99%